Study of Tbilisi City Atmosphere Pollution with PM2.5 and PM10-Microparticles During COVID-19 Pandemic Period - Kukhalashvili, Vephia G.; Pipia, Mikheil G.; Gigauri, Natia G.; Surmava, Aleksandre A.; Intskirveli , Liana N. (Journals of Georgian Geophysical Society, 2022)
Temporal and spatial variations of PM2.5 and PM10 concentrations in Tbilisi city atmosphere during pandemic period (2020-2021) are studied through analysis of routine observations, experimental measurement data, and numerical modeling. Maximum, minimum and average monthly values of concentrations are determined. It is shown that hourly variation of concentration is characterized with two maximums in the intervals between 9-10 and 18-21 hours and by one minimum from 0 to 6 h. It is established that measures related to “Lockdown” cause significant reduction of microaerosols concentration in urban air. It is shown that a change of their concentrations varies near the average values peculiar for automobile roads. Sharp increase of concentration values is observed at some road sections that is caused by local ecological conditions. Kinematics of PM2.5 and PM10 concentration changes induced by motor transport at Tbilisi city territory is explored using 3D model of admixture transfer-diffusion in the atmosphere. Diurnal pattern of dust spatial distribution is studied. Concentration values obtained via modeling are within the limits of values received through routine observations. It is established that a disposition of heavily polluted areas depends on motor transport traffic intensity, highways location, and local circulation systems formed by the dynamic influence of terrain and diurnal change of thermal regime at the underlying surface.